Relationship of Serum Antileishmanial Antibody With Development of Visceral Leishmaniasis, Post-kala-azar Dermal Leishmaniasis and Visceral Leishmaniasis Relapse - Mondal, Dinesh; Ghosh, Prakash; Chowdhury, Rajashree; Halleux, Christine; Ruiz-Postigo, Jose A.; Alim, Abdul; Hossain, Faria; Khan, Md Anik Ashfaq; Nath, Rupen; Duthie, Malcolm S.; Kroeger, Axel; Matlashewski, Greg; et al. (Frontiers in Microbiology, 2019)
To sustain the achievement of kala-azar elimination program, early detection and treatment of the visceral leishmaniasis (VL) cases and associated modalities such as treatment failure (TF), relapse VL (RVL) and Post-kala-azar dermal leishmaniasis (PKDL) is the cornerstone. A predictive biomarker for VL development and related complications could also play a crucial role in curtailing disease incidence and transmission. Investigations to find a biomarker with prospective capabilities are, however, scarce. Using samples and known clinical outcomes generated within two previous longitudinal cohort studies, we aimed to determine if fluctuations in serum anti-rK39 antibody levels could provide such predictive value. Serum samples collected at four different time points (Baseline, 12, 18, and 24 months) from 16 patients who had developed VL within the monitoring period and 15 of their asymptomatic healthy controls counterparts were investigated. To investigate potential prediction of VL related complications, serum samples of 32 PKDL, 10 RVL, 07 TF, and 38 cured VL from a single dose AmBisome trial were analyzed. Of this second panel, all patients were monitored for five years and sera were collected at four time points (Baseline then 1, 6, and 12 months after treatment). The level of anti-rK39 antibodies in archived samples was measured by a semi-quantitative ELISA. The mean antibody level was significantly higher in VL patients compared to their asymptomatic healthy counterparts at each time point. Likewise, we observed a trend toward elevations in antibody levels for PKDL, RVL, TF relative to the reducing levels observed in cured VL. ROC analysis found a promising predictive power of rK39 antibody levels to reveal progression from asymptomatic L. donovani infection stage to VL, defined as 87.5% sensitive and 95% specific. Following treatment, rk39 antibody notably showed 100% sensitivity and 95% specificity in predicting TF. Our data indicate that the relative quantity of serum anti-rK39 antibody has promise within either a predictive or prognostic algorithm for VL and VL-related modalities. These could enable VL control programs to implement more effective measures to eliminate the disease. Further research is, however, imperative to standardize the rK39 antibody ELISA between sites prior to broader use.